2014
DOI: 10.1371/journal.pone.0104677
|View full text |Cite
|
Sign up to set email alerts
|

Low Physical Activity Level and Short Sleep Duration Are Associated with an Increased Cardio-Metabolic Risk Profile: A Longitudinal Study in 8-11 Year Old Danish Children

Abstract: BackgroundAs cardio-metabolic risk tracks from childhood to adulthood, a better understanding of the relationship between movement behaviors (physical activity, sedentary behavior and sleep) and cardio-metabolic risk in childhood may aid in preventing metabolic syndrome (MetS) in adulthood.ObjectiveTo examine independent and combined cross-sectional and longitudinal associations between movement behaviors and the MetS score in 8-11 year old Danish children.DesignPhysical activity, sedentary time and sleep dura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
156
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 121 publications
(170 citation statements)
references
References 51 publications
10
156
4
Order By: Relevance
“…Other likely explanations of this paradoxical finding include reasons related to the structure of the data, 28 regression of BMI/waist circumference to the mean as participants grew older, and possible reverse causation between accelerometry counts (that determine ST time) and BMI or body fat mass. 29 Accelerometer-assessed ST was not associated with adiposity in earlier cross-sectional analyses, 16 although greater waist circumference 14 and greater body fat mass 30 at baseline have been associated with longitudinal increases of ST 14 in other studies, a finding we did not confirm.…”
Section: Discussioncontrasting
confidence: 81%
“…Other likely explanations of this paradoxical finding include reasons related to the structure of the data, 28 regression of BMI/waist circumference to the mean as participants grew older, and possible reverse causation between accelerometry counts (that determine ST time) and BMI or body fat mass. 29 Accelerometer-assessed ST was not associated with adiposity in earlier cross-sectional analyses, 16 although greater waist circumference 14 and greater body fat mass 30 at baseline have been associated with longitudinal increases of ST 14 in other studies, a finding we did not confirm.…”
Section: Discussioncontrasting
confidence: 81%
“…Total PA: VERY LOW m 1/7 studies reported favourable associations (Janz et al 2005); 2/7 studies reported mixed favourable and null associations White and Jago 2012); 4/7 studies reported null associations (Butte et al 2007a;Basterfield et al 2012;Hjorth et al 2014aHjorth et al , 2014b) VPA: 2/3 studies reported favourable associations (total and bouts, Janz et al 2005; dose-response trend, Carson et al 2014); 1/3 studies reported null associations (Butte et al 2007a) MVPA: 2/7 studies reported favourable associations (Janz et al 2009;Mitchell et al 2013); 2/7 studies reported mixed favourable and null associations Hjorth et al 2014b); 3/7 studies reported null associations (Stevens et al 2007;Hallal et al 2012;Hjorth et al 2014a) MPA: 2/2 studies reported null associations (total and bouts, Janz et al 2005;Butte et al 2007a) LPA: 2/3 studies reported null associations (Butte et al 2007a;Treuth et al 2009); 1/3 studies reported an unfavourable association, with evidence of dose-response gradient )…”
Section: No Serious Imprecisionmentioning
confidence: 99%
“…Among longitudinal studies, associations between total PA and adiposity were mixed: 3/7 studies reported at least 1 favourable association (Janz et al 2005;Riddoch et al 2009;White and Jago 2012), and 6/7 studies reported at least 1 null association (Janz et al 2005;Butte et al 2007a;Riddoch et al 2009;Basterfield et al 2012;White and Jago 2012;Hjorth et al 2014aHjorth et al , 2014b. Approximately half of the longitudinal studies that examined VPA (2/3 studies; Janz et al 2005;Carson et al 2014) and/or MVPA (4/7 studies; Janz et al 2009;Riddoch et al 2009;Mitchell et al 2013;Hjorth et al 2014b) reported a favourable prospective association with at least 1 measure of adiposity.…”
Section: S203 Published By Nrc Research Pressmentioning
confidence: 99%
See 2 more Smart Citations